DIPG-51. BLACKFYNN: A SECURE, CLOUD-BASED PLATFORM FOR SHARING AND ANALYZING RESEARCH READY DATA FOR PEDIATRIC CNS CANCERS. Issue 2 (22nd June 2018) - Johnson, Courtney; Christini, Amanda; Felmeister, Alex; Baglieri, Chris; Kambhampati, Madhuri; Waanders, Angela; Mason, Jennifer; Packer, Roger; Resnick, Adam; Nazarian, Javad
Abstract: INTRODUCTION: Sharing research ready data between multiple institutions and across different platforms is a lengthy and cumbersome process which can delay research and potentially negatively impact patient care. Despite the recent surge in generating the genomic and molecular profiles of CNS cancers, correlation of this data with clinical or radiographic data is yet to be streamlined. To address this, CBTTC has partnered with Blackfynn, to develop their HIPAA-compliant, cloud-based platform for integration of histopathology, clinical, molecular, and neuroimaging data. This collaboration provides research ready data that can be easily accessed by clinicians and researchers across different institutions. METHODS: MR imaging, genomic, histological data from a cohort of CBTTC patients diagnosed with midline gliomas were used in a pilot trial. The Blackfynn platform was used to share and annotate MR imaging and histological staining across two academic institutions. Clinicians, basic researchers, and software engineers participated in the project with the goal of integrating a multi-disciplinary, cross-data integration platform. RESULTS: The Blackfynn platform successfully allowed sharing and annotation of neuroimages as well as histopathology slides pertaining to the CBTTC cohort. The neuroimaging on the platform is interactive and can be viewed in axial, coronal and sagittal planes. The pathology slides are also interactive and can be viewed up to 50x magnification. Annotations can be made on all of the multimodal data with the possibility of localizing MR images with the corresponding pathology slides. In conclusion, Blackfynn provides the research community research ready data that is easily uploaded and shared between different institutions.